The Quality Management System - A New Approach to The Continuous Improvement of The Quality of Audit Missions - Sergiu SOIMU; Galina BADICU; Veronica GROSU (Communications of International Proceedings, 2023)
Regulatory norms are periodically renewed. In this regard, International Standards on Auditing (ISA), including quality standards, are no exception as they continue to generate increased interest in the current context. Therefore, the International Auditing and Assurance Standards Board (IAASB) has published a set of new and revised standards on their website, to be implemented starting from December 15, 2022. These standards aim to strengthen and modernize the audit entity's approach to quality management, based on risk, for the development of audit policies and procedures. The purpose of this research is to present the most relevant information regarding the preparation of quality management systems in accordance with the new requirements of ISA, as well as to highlight the main modifications compared to the previous standards and their impact on audit entities. Various regulations and literature sources in the field have been studied to achieve this goal. To assess the scientific performance of the researched field at the international level, an exhaustive search was conducted in databases such as Web of Science and Scopus, using Biblioshiny and EBSCO software. The research results contribute to the development of theory and practice in audit missions, which will enrich the specialized literature in the field and enhance the efficiency of the research process.
Keywords: audit mission; quality management system; quality risks; ISQM 1.